Growth, Stoichiometry, and Palatability of Suaeda salsa From Different Habitats Are Demonstrated by Differentially Expressed Proteins and Their Enriched Pathways - Song, Ye; Liu, Jiayuan; Wang, Jianzhong; Liu, Fude (Frontiers in Plant Science, 2021)
Suaeda salsa (L.) Pall., a medicinal and edible plant, has green and red-violet ecotypes that exhibit different phenotypes, tastes, and growth characteristics. However, few studies have focused on these differences from the aspect of differentially expressed proteins under the conditions of different habitats in the field. In this study, two ecotypes of S. salsa from the intertidal (control) and supratidal (treatment) habitats of the Yellow River Delta were selected. A total of 30 individual leaves were mixed into six samples (three biological replicates for each) and subjected to protein extraction by using tandem mass tag-labeled quantitative proteomic technology. A total of 4771 proteins were quantitated. They included 317 differentially expressed proteins (2.0-fold change, p < 0.05), among which 143 were upregulated and the remaining 174 were downregulated. These differentially expressed proteins mainly participated in biological processes, such as response to stimulus, stress, and biotic stimulus; in molecular functions, such as methyltransferase activity, transferase activity, one-C group transfer, and tetrapyrrole binding; and in cell components, such as non-membrane-bound organelles, intracellular non-membrane-bound organelles, chromosomes, and photosystems. The differentially expressed proteins were mainly enriched in eight pathways, among which the ribosome, phenylpropanoid biosynthesis, and photosynthesis pathways had higher protein numbers than the other pathways. The upregulation of differentially expressed proteins related to the ribosome and photosynthesis increased the relative growth rate and reduced the N:P ratio of S. salsa from the supratidal habitat, thereby improving its palatability. By contrast, most of the differentially expressed proteins involved in phenylpropanoid biosynthesis were downregulated in S. salsa from the intertidal habitat. This result indicated that S. salsa from the intertidal habitat might accumulate flavonoids, lignin, and other secondary metabolites in its leaves that confer a bitter taste. However, these secondary metabolites might increase the medicinal value of S. salsa from the intertidal habitat. This work could provide a theoretical basis and data support for the sustainable and high-value utilization of medicinal and edible plants from coastal wetlands.